Ultra-high yield strength bulk nanocrystalline medium-entropy VCoNi alloy and preparation method thereof
Through the combination of arc smelting, cold rolling, heat treatment, inert gas condensation and ultra-high pressure compression, the preparation of high-purity bulk nanocrystalline VCoNi alloys is solved, and high-performance materials with a yield strength of 3.4GPa are achieved.
Patent Information
- Application Number
- CN202310052612.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-02
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-02-02
AI Technical Summary
At present, there is a lack of mature preparation methods to prepare bulk nanocrystalline VCoNi medium-entropy alloys with high purity and average grain size less than 50 nm, resulting in the failure to fully exert their yield strength.
The combination of arc smelting, cold rolling, heat treatment, inert gas condensation and ultra-high pressure compression was used to prepare a bulk nanocrystalline VCoNi alloy with high purity, uniform tissue, and average grain size less than 50 nm.
A block medium-entropy VCoNi nanocrystalline alloy with a yield strength of up to 3.4 GPa was successfully prepared, which significantly improved the mechanical properties of the material and expanded its application prospects.
Smart Images

Figure CN116162841B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nanocrystal manufacturing and powder metallurgy, and in particular to an ultra-high yield strength bulk nanocrystal medium-entropy VCoNi alloy and a preparation method thereof. Background Art
[0002] Metal materials have become indispensable engineering structural materials due to their excellent machinability, high reusability and excellent mechanical properties. However, with the further development of human society, the requirements for the performance of metal materials are also increasing. Designing and preparing metal materials with better performance has always been the goal pursued by the materials industry. Organization nano-sizing is considered to be an effective means to greatly improve the performance of metal materials. However, the current mainstream preparation methods (multi-pass rolling, high-pressure torsion, equal-diameter angular extrusion, cold drawing, and high-energy ball milling combined with powder sintering) cannot be universally used to prepare metal nanocrystalline bulk materials with high purity and an average grain size of less than 50nm.
[0003] In recent years, medium-high entropy alloys have become a hot topic of current research due to their many excellent physical and chemical properties. They are a new type of metal structural material with broad market application prospects. VCoNi medium-entropy alloys have excellent mechanical properties due to their large lattice distortion effect and Hall-Petch coefficient: the yield strength is as high as nearly 1GPa when the average grain size is 1μm. How to effectively improve its mechanical properties through reasonable and scientific organizational regulation is the key to promoting the future development and application of this type of material.
[0004] After searching, the Chinese patent document with publication date of December 16, 2022 and publication number CN 115478201 A discloses a dual ordered phase CoNiV-based medium entropy alloy and its preparation method. This patent successfully prepared a CoNiV-based medium entropy alloy with a dual ordered phase based on arc melting and heat treatment process mainly by regulating the content of Al and Ti elements. The medium entropy alloy prepared by this method has good yield strength, which can reach 1.2GPa. However, due to the limitations of the traditional arc melting preparation process, the grain size of the alloy material is still at the micron level, and the advantage of the large Hall-Petch coefficient of the VCoNi medium entropy alloy cannot be brought into play. If the grain size can be further refined to the nanometer level through some specific preparation means, the yield strength of the material is expected to be significantly improved, thereby expanding its application prospects.
[0005] A Chinese patent document with a publication date of April 16, 2021 and a publication number of CN 112663333 A was also retrieved, which discloses a method for depositing ultrafine metal powders. In this method, in an atmosphere of inert gas protection, a metal target is excited by laser heating to prepare nanoparticles with uniform and controllable size and regular shape. This patent mainly proposes a preparation process for pure metal nanopowders, and has not yet explored the preparation process for bulk nanometals.
[0006] A Chinese patent document with a publication date of November 11, 2022 and a publication number of CN 115323241 A was also retrieved, which discloses a method for preparing a nano refractory high entropy alloy TiZrHfNb. This method successfully prepares a single-phase BCC structured nanocrystalline material with uniform organization and excellent thermal stability by an inert gas condensation method. This patent adds a high-pressure process on the basis of the Chinese patent process with publication number CN112663333 A, and successfully prepares a bulk nanometal material. However, among the four elements in the alloy system jointly disclosed in this patent, the melting points of Ti and Zr are close, the melting points of Hf and Nb are close, and there is no obvious lattice distortion effect, so it is easier to prepare a bulk nanocrystalline material with uniform organization. For the VCoNi alloy system, since the melting point of the V element is much higher than that of the Co element and the Ni element, and there is a large lattice distortion effect, the relevant preparation process still needs further exploration.
[0007] A Chinese patent document with a publication date of May 31, 2022 and a publication number of CN 112251644 B was also retrieved, which disclosed a method for preparing equiaxed nanocrystalline Ti6Al4V-Ag alloy with high thermal stability. The patent mainly refines the grains by the ECAP method, but this method has a significant disadvantage: it is impossible to prepare bulk materials with a grain size less than 50nm, and thus it is impossible to study its various physical and chemical properties, which seriously retards the development of its strengthening and toughening theory and industrial application.
[0008] In summary, although metal bulk nanocrystalline materials can be prepared by certain means, there is currently no mature and available preparation method for the preparation of high-purity FCC structure VCoNi medium-entropy alloys with large lattice distortion. Summary of the invention
[0009] The purpose of the present invention is to provide an ultra-high yield strength bulk nanocrystalline medium-entropy VCoNi alloy and a preparation method thereof, which solves the problem mentioned in the background technology that although metal bulk nanocrystalline materials can be prepared by certain means, there is currently no mature and available preparation method for the preparation of high-purity FCC structure VCoNi medium-entropy alloys with large lattice distortion.
[0010] In view of the shortcomings of the above-mentioned prior art, in order to improve the problem of large grain size and low purity of the prepared material, and then realize the preparation of high-purity ultra-high yield strength face-centered cubic medium-entropy nanocrystalline VCoNi alloy bulk material. The patent of the present invention provides a means of combining arc melting, cold rolling, heat treatment, inert gas condensation and ultra-high pressure compression to realize the preparation of nanocrystalline medium-entropy VCoNi alloy with nanoscale grain size bulk material. This method can successfully prepare high-purity, uniform structure, average grain size less than 50nm, and yield strength up to 3.4GPa bulk medium-entropy VCoNi nanocrystalline alloy. The successful preparation of this alloy has laid a good foundation for the application of this material and the development of related theories of nanocrystalline materials.
[0011] To achieve the above-mentioned object, the present invention provides the following technical solutions: an ultra-high yield strength bulk nanocrystalline medium-entropy VCoNi alloy and a preparation method thereof, wherein the nanocrystalline medium-entropy VCoNi alloy is an ultra-high yield strength alloy, the microstructure is mainly nanocrystalline, and the bulk medium-entropy VCoNi nanocrystalline alloy is high in purity, uniform in structure, with an average grain size of less than 50nm and a yield strength of up to 3.4GPa;
[0012] The chemical elements in the VCoNi alloy are in the following ratio: V:Co:Ni=1:1:1; and the purity of each pure element in the smelting parent material is ≥99.95%;
[0013] The specific steps are as follows:
[0014] First, a high-purity equiatomic ratio coarse-grained VCoNi bulk material is prepared in an arc melting furnace, and then the prepared bulk material structure is homogenized by a combination of cold rolling and heat treatment to obtain a target material, and finally a bulk nanocrystalline material is prepared by laser inert gas condensation and in-situ ultrahigh pressure;
[0015] Second, the arc melting furnace was repeatedly cleaned three times with high-purity argon gas before smelting, and the vacuum degree was maintained at 1.5×10 -3 Pa; the rolling amount during the homogenization process is 50%-80%, and the annealing parameters are 1000-1200℃, 3-6h;
[0016] Third, the inert gas condensation chamber is kept in a high vacuum state (less than 10 -6Pa), after high-purity helium is introduced, the pressure in the cavity is kept stable between 400-600Pa, the distance between the laser emission lens and the target is controlled between 70-80cm, the emission power is between 50-100W, and a picosecond laser of 808-1064nm is selected to ensure that the single pulse energy exceeds 100μJ, the pulse frequency is 500kHz, and the pulse width is less than 15ps; the powder is pre-pressed under a pressure of 500-800MPa, and finally the sample is pressed into a block sample with a diameter of 10mm and a thickness of 0.2-0.3mm under a pressure of 5-6GPa at room temperature.
[0017] The raw materials used in the preparation of the VCoNi alloy are all high-purity bulk materials with a purity exceeding 99.95%, and the quality accuracy of each raw material is controlled within 5×10 -4 Within g.
[0018] The present invention also discloses a method for preparing ultra-high yield strength bulk nanocrystalline medium entropy VCoNi alloy, characterized in that the specific steps are as follows:
[0019] S1: Calculate the required mass of each element according to the equiatomic ratio, polish the raw material surface to remove the possible oxide layer on the surface, and then weigh it in a high-precision balance. Then prepare an equiatomic bulk sample in an arc melting furnace (considering that the melting point of V element is significantly higher than that of the other two elements, the three raw materials should be placed above the other two raw materials when they are placed in the melting chamber to ensure that the elements of the prepared sample are evenly distributed). Repeat the melting six times to ensure that the elements in the prepared material are evenly distributed.
[0020] S2: homogenizing annealing the bulk equiatomic ratio VCoNi medium entropy alloy prepared in step 1 at 1100°C for 10h, followed by cold rolling;
[0021] S3: The alloy flake material prepared above is deposited into a nanocrystalline powder material by an inert gas condensation method and is prepared into a bulk material by in-situ ultrahigh pressure. The specific process is as follows:
[0022] ① Clean the entire chamber carefully to avoid contamination, and place the bulk material (target material) prepared in step 2 on the sample tray in the chamber;
[0023] ② The inert gas condensation chamber is pumped to an ultra-high vacuum state through a primary pump (mechanical pump) and a secondary pump (molecular pump), and then high-purity helium is flushed into the chamber and liquid nitrogen is flushed into the cold trap;
[0024] ③ Set the position and adjust the angle of the laser so that the light path is perpendicular to the target, and adjust the distance between the laser and the sample;
[0025] ④ Set the laser power and conduct a short test experiment to ensure that the laser evaporation, cold trap deposition and scraper collection of the powder can be successfully achieved after the laser interacts with the bulk material;
[0026] ⑤ After ensuring that there are no problems in step ④, start the powder preparation experiment and observe the powder making process through the observation window;
[0027] ⑥ After collecting enough powder, the powder collection tank is transferred in situ to the low-pressure chamber. Then the sample is placed on the lower pressure head and transferred in situ to the high-pressure chamber. The pressure is applied at 5 GPa for 3 minutes, and finally a high-purity bulk nanocrystalline material is successfully prepared.
[0028] As a preferred embodiment of the present invention, when the three raw materials in S1 are placed in the smelting chamber, the V element should be placed above the other two raw materials to ensure uniform element distribution of the prepared sample.
[0029] As a preferred embodiment of the present invention, the rolling amount in S2 is controlled at 60%, and then annealing is performed at 1000° C. for 3 h in a vacuum environment to ensure that a block material with uniform microstructure is obtained.
[0030] As a preferred embodiment of the present invention, the vacuum degree of S3 in ② is less than 10 -6 Pa.
[0031] As a preferred embodiment of the present invention, in step ⑤ of S3, the nanopowders deposited on the cold trap are scraped off with a scraper in a timely manner and collected in a powder collecting tank.
[0032] As a preferred embodiment of the present invention, the pre-pressing is performed at a pressure of 500 MPa in ⑥ of S3.
[0033] As a preferred embodiment of the present invention, the smelting is repeated six times to ensure uniform distribution of elements in the prepared material.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The beneficial effects of the present invention are:
[0036] a. It is difficult to prepare high-purity bulk nanocrystals with an average grain size of less than 50nm using traditional bulk nanocrystal preparation technology. The entire preparation process of this preparation scheme is completed in an ultra-high vacuum chamber, and there is no oxidation of the sample. This can greatly avoid the influence of impurity elements on sample performance, and plays a significant role in the development of nanocrystal theory and engineering applications.
[0037] b. The present invention can prepare nanocrystalline VCoNi medium-entropy alloys with uniform organization and large lattice distortion. Multiple measures are taken during the preparation process to ensure uniform organization of the prepared nanocrystalline bulk material: the V element is placed above the other two elements during the raw material smelting stage; a large cold rolling deformation of 60% and an annealing temperature of 1100°C calculated based on phase diagram theory are used during the organization homogenization stage; a high-power laser is used during the inert gas condensation stage to uniformly excite the target material, so that the atoms are uniformly excited to prepare a uniformly organized bulk nanocrystalline material.
[0038] c. Compared with traditional chemical preparation methods, this preparation method is relatively simple and does not involve many complicated preparation processes. On the other hand, this preparation process does not contain any reagents with safety risks, and its safety factor is much higher than the currently reported chemical methods.
[0039] d. The yield strength of the nanocrystalline VCoNi medium-entropy alloy prepared by the present invention is as high as 3.4 GPa, which is more than twice the currently reported value of materials in this system, greatly expanding the potential engineering application prospects of such materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0041] Figure 1 It is a schematic diagram of the inert gas condensation device.
[0042] Figure 2 This is the XRD spectrum of the prepared nanocrystalline VCoNi medium-entropy alloy.
[0043] Figure 3 These are the TEM characterization results and grain size distribution diagram of the as-prepared nanocrystalline VCoNi medium-entropy alloy: (a) bright field image; (b) grain size distribution diagram.
[0044] Figure 4 is the true stress-strain curve for compression. DETAILED DESCRIPTION
[0045] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0046] Embodiment 1:
[0047] See also Figure 1-2The present invention provides a technical solution: an ultra-high yield strength bulk nanocrystalline medium entropy VCoNi alloy and a preparation method thereof, wherein the nanocrystalline medium entropy VCoNi alloy is an ultra-high yield strength alloy having a single-phase FCC structure, a high purity, uniform organization, an average grain size of less than 50 nm, and a yield strength of up to 3.4 GPa.
[0048] The chemical elements in the VCoNi alloy are in the following ratio: V:Co:Ni=1:1:1; and the purity of the single element of the smelting parent material is ≥99.95%;
[0049] The specific steps are as follows:
[0050] First, high-purity equiatomic coarse-grained VCoNi bulk material was prepared in an arc melting furnace. Then, the prepared bulk material structure was homogenized by combining cold rolling and heat treatment to obtain the target material. Finally, bulk nanocrystalline material was prepared by laser inert gas condensation and in-situ ultrahigh pressure. Before melting, the arc melting furnace was repeatedly cleaned three times with high-purity argon gas, and the vacuum degree was maintained at 1.5×10 -3 Pa; the rolling amount during the homogenization process was 50%-80%, and the annealing parameters were 1000-1200℃, 3-6h; before the experiment, the inert gas condensation chamber was kept in a high vacuum state (less than 10 -6 Pa), after high-purity helium is introduced, the pressure in the cavity is kept stable between 400-600Pa, the distance between the laser emission lens and the target is controlled between 70-80cm, the emission power is between 50-100W, and a picosecond laser of 808-1064nm is selected to ensure that the single pulse energy exceeds 100μJ, the pulse frequency is 500kHz, and the pulse width is less than 15ps; the powder is pre-pressed under a pressure of 500-800MPa, and finally the sample is pressed into a block sample with a diameter of 10mm and a thickness of 0.2-0.3mm under a pressure of 5-6GPa at room temperature. The raw materials used in the preparation of VCoNi alloy are all high-purity block materials with a purity of more than 99.95%, and the quality accuracy of each raw material is controlled within 5×10 -4 Within g.
[0051] This embodiment also discloses a method for preparing ultra-high yield strength bulk nanocrystalline medium entropy VCoNi alloy, the specific steps are as follows:
[0052] S1: Calculate the required mass of each element according to the equiatomic ratio, polish the raw material surface to remove the possible oxide layer on the surface, and then weigh it in a high-precision balance. Then prepare an equiatomic bulk sample in an arc melting furnace (considering that the melting point of V element is significantly higher than that of the other two elements, the three raw materials should be placed above the other two raw materials when they are placed in the melting chamber to ensure that the elements of the prepared sample are evenly distributed). Repeat the melting six times to ensure that the elements in the prepared material are evenly distributed.
[0053] S2: homogenizing annealing the bulk equiatomic ratio VCoNi medium entropy alloy prepared in step 1 at 1100°C for 10h, followed by cold rolling;
[0054] S3: The alloy flake material prepared above is deposited into a nanocrystalline powder material by an inert gas condensation method and is prepared into a bulk material by in-situ ultrahigh pressure. The specific process is as follows:
[0055] ① Clean the entire chamber carefully to avoid contamination, and place the bulk material (target material) prepared in step 2 on the sample tray in the chamber;
[0056] ② Pump the inert gas condensation chamber to an ultra-high vacuum state through the primary pump (mechanical pump) and the secondary pump (molecular pump), and the vacuum pressure value is <10 -6 Pa, then high-purity helium is flushed into the cavity and liquid nitrogen is flushed into the cold trap;
[0057] ③ Set the position and adjust the angle of the laser so that the light path is perpendicular to the target, and adjust the distance between the laser and the sample;
[0058] ④ Set the laser power and conduct a short test experiment to ensure that the laser evaporation, cold trap deposition and scraper collection of the powder can be successfully achieved after the laser interacts with the bulk material;
[0059] ⑤ After ensuring that there are no problems in step ④, start the powder preparation experiment, observe the powder making process through the observation window, and use a scraper to scrape off the nano powder that has been deposited on the cold trap and collect it in the powder collection tank;
[0060] ⑥ After collecting enough powder, transfer the powder collection tank in situ to the low-pressure chamber, then place the sample on the lower pressure head and transfer it in situ to the high-pressure chamber, use a pressure of 500MPa for pre-pressing, and use a pressure of 5GPa for 3 minutes, and finally successfully prepare high-purity bulk nanocrystalline material.
[0061] When the three raw materials in S1 are placed in the melting chamber, the V element should be placed above the other two raw materials to ensure that the elements of the prepared sample are evenly distributed. During the process, the melting is repeated six times to ensure that the elements in the prepared material are evenly distributed. The rolling amount in S2 is controlled at 60%, and then annealed at 1000℃ for 3h in a vacuum environment to ensure that a block material with uniform microstructure is obtained.
[0062] Experimental example:
[0063] The preparation process of the present invention can be mainly divided into three main processes, namely: smelting of VCoNi medium entropy alloy target material, homogenization of the target material structure, and deposition and high pressure forming of nanoparticles.
[0064] The specific experimental process is as follows:
[0065] (1) Calculate and weigh the mass of each element of VCoNi according to the equal atomic ratio. The purity of each element is greater than 99.95%, and the mass accuracy is controlled within 5×10 -4 Before weighing, the raw materials were ground and polished to remove the possible oxide film on the surface, and then ultrasonically cleaned with alcohol;
[0066] (2) Clean the arc melting furnace cavity and then evacuate the cavity until the vacuum degree reaches 1.5×10 -3 Recoil high-purity argon gas to about 500Pa at 150Pa, and then perform vacuum treatment. This step is repeated three times;
[0067] (3) The weighed and cleaned raw materials are placed in an arc melting furnace (the melting point of V element is much higher than that of the other two elements, so it is placed at the top to ensure the uniformity of the smelting structure). Before smelting, pure Ti is repeatedly smelted three times in the cavity to ensure a lower oxygen content in the cavity, and then VCoNi target is smelted and repeatedly smelted 6 times, and then suction cast into 6×20×18mm 3 of bulk material;
[0068] (4) The above-mentioned suction cast material was homogenized in a vacuum environment at 1100° C. for 10 h, and then the sample was subjected to a cold rolling experiment, with a pressing amount of 5% each time, and the final rolling amount was controlled at about 60%. The material was then recrystallized in a vacuum environment at 1000° C. for 3 h to ensure that a target material with uniform structure was obtained;
[0069] (5) The entire chamber is carefully cleaned to avoid contamination, and the block material (target material) prepared in the previous step is placed on the sample tray in the chamber. The inert gas condensation chamber is pumped to an ultra-high vacuum state (<10 -6 Pa), and then high-purity helium is injected into the cavity, and liquid nitrogen (such as Figure 1 shown);
[0070] (6) Set the position and adjust the angle of the laser so that the light path is perpendicular to the target material. At the same time, adjust the distance between the laser and the sample to 75 cm, set the laser power to 100 W, ensure that the single pulse energy exceeds 100 μJ, the pulse frequency is 500 kHz, and the pulse width is less than 15 ps. Then conduct a short test experiment to ensure that the laser can successfully achieve laser evaporation, cold trap deposition and scraper collection of the powder after the laser interacts with the bulk material;
[0071] (7) After ensuring that there are no problems in the previous step, start the powder preparation experiment, observe the powder preparation process through the observation window, and use a scraper to scrape off the nanopowder that has been deposited on the cold trap and collect it in the powder collection tank;
[0072] (8) After collecting enough powder, the powder collection tank was transferred in situ to the low-pressure chamber and pre-pressed at a pressure of 500 MPa. The sample was then placed on the lower pressure head and transferred in situ to the high-pressure chamber. The pressure was applied at 5 GPa for 3 min, and finally a high-purity bulk nanocrystalline material with a diameter of 10 mm and a thickness of 0.3 mm was successfully prepared.
[0073] like Figure 2-4 The microstructure characterization and mechanical property test of the bulk material prepared above are shown in Figure 1. The single FCC structure is then tested by focused ion beam transmission sample preparation. The specific characterization results are shown in Figure 2. After that, the focused ion beam is used again to prepare small pillars with a diameter of about 2 μm and a height of about 5 μm. Finally, nanoindentation (strain rate 10 -2 s -1 ) characterizes its mechanical properties, with a yield strength of up to 3.4 GPa.
[0074] It should be noted that the present invention is an ultra-high yield strength bulk nanocrystalline medium-entropy VCoNi alloy and its preparation method. Each component is a universal standard component or a component known to technical personnel in this field. Its structure and principle can be known to technical personnel through technical manuals or through conventional experimental methods.
Claims
1. Ultra-high yield strength bulk nanocrystalline medium entropy VCoNi alloy, characterized by: The nanocrystalline medium entropy VCoNi alloy is an ultra-high yield strength alloy with a single-phase FCC microstructure, high purity, uniform organization, an average grain size of less than 50nm, and a yield strength of up to 3.4 GPa. The chemical elements in the VCoNi alloy are in the following ratio: V:Co:Ni=1:1:1; and the purity of each pure element in the smelting parent material is ≥99.95%; The specific steps are as follows: (1) First, prepare high-purity equiatomic ratio coarse-grained VCoNi bulk material in an arc melting furnace. Before melting, the arc melting furnace is repeatedly cleaned three times with high-purity argon gas, and the vacuum degree is maintained at 10000 after each cleaning. Pa; (2) then homogenizing the structure of the prepared block material by a method combining cold rolling and heat treatment to obtain a target material, wherein the rolling amount during the homogenization process is 50%-80%, and the heat treatment is annealing, and the annealing parameters are 1000-1200° C. for 3-6 hours; (3) Finally, bulk nanocrystalline materials were prepared by laser inert gas condensation and in-situ ultrahigh pressure: before the experiment, the inert gas condensation chamber was kept in a high vacuum state with a vacuum pressure value of <10-6 Pa. After high-purity helium was introduced, the pressure in the chamber was kept stable at 400-600 Pa. The distance between the laser emission lens and the target material was controlled to be between 70-80 cm, the emission power was between 50-100 W, and a picosecond laser of 808-1064 nm was selected to ensure that the single pulse energy exceeded 100 μJ, the pulse frequency was 500 kHz, and the pulse width was less than 15 ps. The powder was pre-pressed under a pressure of 500-800 MPa, and finally, the sample was pressed into a bulk sample with a diameter of 10 mm and a thickness of 0.2-0.3 mm at room temperature using a pressure of 5-6 GPa.
2. The ultra-high yield strength bulk nanocrystalline medium entropy VCoNi alloy according to claim 1, characterized in that: The raw materials used in the preparation of the VCoNi alloy are all high-purity bulk materials with a purity exceeding 99.95%, and the quality accuracy of each raw material is controlled within Within g.
3. A method for preparing the ultra-high yield strength bulk nanocrystalline medium entropy VCoNi alloy as described in any one of claims 1-2, characterized in that: The specific steps are as follows: S1: Calculate the mass of each element according to the equiatomic ratio, polish the surface of the raw materials to remove the possible oxide layer on the surface, and then weigh them in a high-precision balance. Then prepare the equiatomic bulk sample in an arc melting furnace. Considering that the melting point of V element is significantly higher than that of the other two elements, the three raw materials should be placed on top of the other two raw materials when they are placed in the melting chamber to ensure that the elements of the prepared sample are evenly distributed. Repeat the melting six times to ensure that the elements in the prepared material are evenly distributed. S2: homogenizing annealing the bulk material equiatomic ratio VCoNi medium entropy alloy prepared in step 1 at 1100°C for 3-6h, followed by cold rolling; S3: The alloy flake material prepared above is deposited into nanocrystalline powder material by laser inert gas condensation method and prepared into bulk material by in-situ ultrahigh pressure. The specific process is as follows: ① Clean the entire chamber carefully to avoid contamination, and place the alloy sheet material prepared in step 2 on the sample tray in the chamber; ② The inert gas condensation chamber is pumped to an ultra-high vacuum state through the primary pump and the secondary pump, and then high-purity helium is flushed into the chamber and liquid nitrogen is flushed into the cold trap; ③ Set the position and adjust the angle of the laser so that the light path is perpendicular to the target, and adjust the distance between the laser and the sample; ④ Set the laser power and conduct a short test experiment to ensure that the laser evaporation, cold trap deposition and scraper collection of the alloy sheet material can be successfully achieved after the laser interacts with the alloy sheet material; ⑤ After ensuring that there are no problems in step ④, start the powder preparation experiment and observe the powder making process through the observation window; ⑥ After collecting enough powder, the powder collection tank was transferred in situ to the low-pressure chamber and pre-pressed at a pressure of 500 MPa. The sample was then placed on the lower pressure head and transferred in situ to the high-pressure chamber. A pressure of 5 GPa was applied for 3 minutes, and finally a high-purity bulk nanocrystalline material was successfully prepared.
4. The method for preparing the ultra-high yield strength bulk nanocrystalline medium entropy VCoNi alloy according to claim 3, characterized in that: In step ④ of S3, the nano powders deposited on the cold trap are scraped off with a scraper at an appropriate time and collected in a powder collecting tank.
Citation Information
Patent Citations
A high thermal stability equiaxed nanocrystalline Ti6Al4V-Ag alloy and its preparation method
CN112251644B
Method for carrying out ultrafine nano metal powder deposition on surface of fabric
CN112663333A
TiZrHfNb nanocrystalline refractory high-entropy alloy and preparation method thereof
CN115323241A
CoNiV-based medium-entropy alloy containing double ordered phases and preparation method of CoNiV-based medium-entropy alloy
CN115478201A
Method for regulating and controlling hydrogen embrittlement resistance and corrosion resistance of entropy alloy in CoNiV
CN111996397A